Creating a sense of “aliveness” in a SoTL CoP on a rural campus - Bernard, E. (South African Journal of Higher Education, 2024)
The Scholarship of Teaching and Learning (SoTL), as a research-based inquiry into student learning, is a continuously evolving practice. SoTL, as a practice, guides academics in improving upon their teaching, which is based on their specific context and student cohort. However, since academics are ultimately specialists in their own fields, completing research based on higher education topics is most often unfamiliar territory; it can, however, be supported through SoTL communities of practice (CoPs). The principles of SoTL and of cultivating CoPs can play a key role in designing these CoPs for “aliveness”. In this action research study, feedback and outputs from the SoTL CoP members at a South African higher education institution indicate that to support researchers optimally, a flexible approach, embedded in an organised schedule and integrated with sound research practices, ensures a sense of “aliveness” for members that participate in the CoP.